A comprehensive ethnobotanical profile of Ocimum campechianum (Lamiaceae): from traditional medicine to phytochemical and pharmacological evidences. (2nd November 2022) - Guardado Yordi, Estela; Matos, Maria J.; Buso, Piergiacomo; Martínez, Amaury Pérez; Asanza, Mercedes; Scalvenzi, Laura; Manfredini, Stefano; Tacchini, Massimo; Radice, Matteo; Sacchetti, Gianni
Abstract: There is extensive ethnobotanical information on Ocimum campechianum as it is widely used by the natives of Central and South America and the Amazon. Although many of its traditional uses have been confirmed, studies are still scarce and scattered. Therefore, the main focus of this review is to provide a comprehensive and critical analysis of the state of the art about ethnobotanical, phytochemical, pharmacological, and toxicological knowledge of O. campechianum . This overview offers a starting point for further studies of possible health applications that meet modern needs for human well-being. Future challenges should be focused on research based on new approaches for the understanding of its global benefits. It is suggested to promote studies on multiple herbal remedies, and the antiproliferative and cytotoxic activities of the compounds, as well as new strategies that relate phytochemistry with bioactivity, toxicological evaluations on acute and long-term toxicity, mechanisms of action, pharmacodynamic, and pharmacokinetic studies. Finally, a focus on the possible application of O. campechianum as a biopesticide for the sustainable protection crop of crops and suggests the need to explore new uses of its essential oil for the treatment of foodborne pathogens.